Entrepreneurial Behavior of SMEs and Characteristics of the Managers of Northwest Mexico - Sergio Ochoa Jiménez; Alma Rocío García García; Beatriz Alicia Leyva Osuna; Sacnicté Valdez del Río (Social Sciences, 2021)
The objective of this study is to determine the difference in the entrepreneurial behavior of companies based on the demographic characteristics of their manager or leader. To comply with the above, a quantitative, transversal, and non-experimental research study was carried out, which consisted in applying an instrument to 262 managers of small and medium enterprises (SMEs) in a northern city in Mexico. The collected information was analyzed in the software SPSS, version 26, with statistical testing by the Mann-Whitney and Kruskal-Wallis tests. The main findings show that these companies have differences in their entrepreneurial behavior based on the age and educational level of their managers, while gender and seniority at work are not differentiating elements in relation to the above. This research generates different possibilities of studies to be carried out in large companies from other sectors, and suggests the inclusion of behavioral characteristics as study variables.